Sex and the City: A Situationist Reading of Jens Jorgen Thorsen’s Film Adaptation of Henry Miller’s Quiet Days in Clichy - Jennifer Cowe (European Journal of American Studies, 2016)
This paper will explore the influence of the Situationist International (SI) philosophy upon Jens Jorgen Thorsen’s film adaptation of Quiet Days in Clichy (1970). Whilst acknowledging the film’s place within a wider changing Danish culture, I will aim to show that the film engages with the key Situationist theories of Dérive, Psychogeography and Détournement and that it reflects contemporary societal issues whilst remaining true to Henry Miller’s anarchic and joyful novella. Thorsen was unarguably one of Denmark’s most inventive and revolutionary filmmakers and Quiet Days in Clichy can be viewed in relation to his engagement with the concepts of the SI.